2018
DOI: 10.1097/imi.0000000000000542
|View full text |Cite
|
Sign up to set email alerts
|

Mini Right Anterior Thoracotomy Approach versus Sternotomy for Resection of Intracardiac Myxoma

Abstract: Objective The standard approach in treating cardiac myxoma is the median full sternotomy. After recent advances in surgical techniques, the mini right anterior thoracotomy has emerged as an alternative method. Methods We performed a retrospective study to compare the clinical outcomes of the mini right anterior thoracotomy approach with those of the sternotomy approach for resection of cardiac myxoma at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Our research revealed 11 studies fulfilling these inclusion criteria, 9–19 producing a pooled data set of 653 patients of whom 294 underwent MI and 359 underwent MS cardiac tumor excision (Table 3) (Figure 1). There was 100% concordance between reviewers equating to a Cohen's kappa coefficient of κ = 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research revealed 11 studies fulfilling these inclusion criteria, 9–19 producing a pooled data set of 653 patients of whom 294 underwent MI and 359 underwent MS cardiac tumor excision (Table 3) (Figure 1). There was 100% concordance between reviewers equating to a Cohen's kappa coefficient of κ = 1.…”
Section: Resultsmentioning
confidence: 99%
“…Given that atrial myxoma was the most frequent cardiac mass, right mini‐thoracotomy was the most utilized minimally invasive access 10,11,14,15,17–19 ; for aortic valve masses a parasternal incision (4–5 cm with rib resection and reattachment) was performed in some cases 11 . Robotic or robotic assisted approach was used in Shilling, 12 Yang, 13 and Moss 16 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy showed excellent results with short hospital stay, low intraoperative blood loss as well as cosmetically appealing outcome associated with less invasive treatment. 8 Thus, minimally invasive surgery might even improve reconvalescence after surgery and mortality that was described to be under 5% in conventionally operated patients. 9,10…”
Section: Discussionmentioning
confidence: 99%
“…For large septal defects, reconstruction with bovine pericardium can easily be performed [16]. Depending on surgeon experience, preference, and tumor location, a right thoracotomy approach to either the left or right atrium can be considered [63]. While a left atrial approach has been described for tumors on the left atrial side of the intra-atrial septum, if such an approach is chosen, it is critical that the principles of complex tumor excision, including the stalk and septal roots (with reconstruction of the intra-atrial septum if necessary), be maintained [64].…”
Section: Surgical Management Of Benign Cardiac Tumorsmentioning
confidence: 99%